The role of higher education socialization in shaping students' future-oriented work ethic - Sütő, Zsuzsanna; Dusa, Ágnes Réka; Dabney-Fekete, Ilona Dóra; Demeter-Karászi, Zsuzsanna (Central European Journal of Educational Research, 2026)
Research on higher education clearly indicates that the institutional environment, as well as the relationships formed with faculty and peers, not only influence academic achievement and the risk of dropout, but also have a significant long-term effect on students' life trajectories, future outlook, future orientation, and even their decisions to remain in a given geographic location (Pusztai, 2011; Bess & Dee, 2012; Sütő, 2021; Sütő, 2025; Demeter-Karászi, 2025). This suggests that higher education institutions do not operate merely as knowledge-transfer organizations, but also as socializing environments that shape students' relationship with work, achievement, and long-term goals. The theoretical framework of our research is therefore grounded in approaches that interpret future-oriented work ethic not exclusively as an individual psychological trait, but as a phenomenon embedded in social relationships and institutional contexts (Berger, 2001; Kuh & Umbach, 2004). Our research seeks to answer what associations can be identified between the characteristics of the social and institutional environment of higher education institutions — in particular, institutional culture, relationships with faculty and peers, and institutional trust — and students' future-oriented work ethic. Our empirical data are drawn from the 2023–2024 survey of the MTA–DE Public Education Development Research Program, a large-scale international database comprising 1,336 respondents. The results indicate that trust-based relationships with both faculty and peers, as well as the perception of a transparent and fair institutional atmosphere, are significantly associated with higher levels of future-oriented work ethic, with perceived supportive institutional culture emerging as the strongest predictor (β = 0.252; p < 0.001). It is particularly noteworthy that the effect of institutional and relational factors persisted even after controlling for social background variables. Our findings thereby corroborate the theoretical stance that future-oriented work ethic is not solely derived from individual attributes, but can be understood as an orientation shaped during higher education socialization through institutional and social environments. This is an especially important finding in light of the growing heterogeneity of the student body, as it suggests that a supportive institutional culture may contribute to strengthening the future orientation and long-term academic success of students from diverse social backgrounds.